The linguacultural aspect of translating kazakh language’s realia into japanese language. (based on translation of «aғaш бесіктен жер бесікке дейін») (Journal of Oriental Studies, 2019)
The program “Ruhani Zhangyru” launched by President Nursultan Nazarbayev in Kazakhstan shouldn’t only spread inside of the country, but also abroad. For this purpose, the translation of our literature works plays a major role. While translating literature works especially about culture, the realia from these works will be the main problem for a translator. Realia are words and expressions for culturespecific material elements. Because while translating this kind of culturespecific items there frequently occurs a problem when the target language lacks a suitable equivalence for realia in the source language. In this work, we will discuss some strategies of translating realia from the Kazakh language to the Japanese language by real examples. And will make some analysis for how the cultural overtones maintained during this process. Key words: translation, realia, equivalent, strategies of translation, culture, linguacultural.